Generosity and Resilience: Transnational Activity among the Khmer of Norway - Overland, Gwynyth Jones; Yenn, Virak (Refuge: Canada's Journal on Refugees, 2007)
The article reports on the pilot phase of an ongoing study of successfully rehabilitated Khmer refugees. Some of the most striking recoveries in this heavily traumatized group have taken place among those who have focused on contributing to the rebuilding of Cambodia. The article explores this collective and individual transnational generosity both generally, as an aspect of survivor resilience, and specifically by following one process. Why do Khmer refugees want to build a school and what does it mean to them? How does their transnational generosity relate to the resilience of Khmer refugees? Their own explanations are founded in their religion.